Konstitusionalitas Efisiensi Anggaran Melalui Instruksi Presiden Nomor 1 Tahun 2025 Terhadap Dana Keistimewaan Yogyakarta Tahun 2025 - syifaa afelyna suryoputri; Alan Bayu Aji (JURNAL RECHTENS, 2026)
The legal issue examined in this study concerns the constitutional limits on using a Presidential Instruction as a policy rule to implement budget efficiency measures when such measures affect Intergovernmental Transfers (TKD) and the Special Fund for the Special Region of Yogyakarta (Dana IS). This study aims to assess the constitutionality of Presidential Instruction No. 1 of 2025 in governing TKD efficiency and its implications for Dana IS. This is a normative legal study. The findings indicate that a Presidential Instruction is justifiable insofar as it regulates the procedures for budget execution without materially altering the TKD configuration stipulated in the State Budget Law. However, implementing the Instruction through subordinate instruments that create a “reserve” scheme may effectively reduce regional fiscal entitlements and function as a concealed budget revision, thereby conflicting with the principle of legality and undermining Parliament’s budgetary authority. Because Dana IS specifically supports asymmetric decentralization, any effective reduction in its funding may also be inconsistent with the constitutional requirement of fair and harmonious central–regional fiscal relations and the statutory commitment to financing Yogyakarta’s special status.